1995
DOI: 10.1128/jvi.69.10.6149-6157.1995
|View full text |Cite
|
Sign up to set email alerts
|

Induction of accelerated feline immunodeficiency virus disease by acute-phase virus passage

Abstract: Development of feline immunodeficiency virus (FIV) infection in cats as a small animal model for lentiviral immunodeficiency disease has been hampered by the prolonged and variable disease course following experimental infection. To address this issue, we generated high-titer, unselected FIV stocks by pooling plasma from cats acutely infected with a subgroup C FIV isolate designated CABCpadyOOC (FIV-C-PGammer). Subsequent infection with this virus pool resulted in rapidly progressive, fatal disease in greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…Histological evidence suggests that some lions biopsied may have progressed to a chronic stage of infection or undergone atrophy of the lymph nodes, another consequence of pathologic immunodeficiency virus infections (Brown et al, 1991;Diehl et al, 1995;McClure et al, 1989;Quijano et al, 1997;Wang et al, 2003). In 2 lions, histopathology of lymphoid tissues (lymph nodes and spleen) was consistent with a progressive depletion of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological evidence suggests that some lions biopsied may have progressed to a chronic stage of infection or undergone atrophy of the lymph nodes, another consequence of pathologic immunodeficiency virus infections (Brown et al, 1991;Diehl et al, 1995;McClure et al, 1989;Quijano et al, 1997;Wang et al, 2003). In 2 lions, histopathology of lymphoid tissues (lymph nodes and spleen) was consistent with a progressive depletion of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…FIV is an important natural model for HIV/AIDS since FIV-infected cats develop AIDS-like illnesses (Pedersen et al, 1987;Willett et al, 1997). As with HIV and SIV infection, lymphadenopathy, immunodeficiency, progressive lymphoid depletion, associated oral manifestations, loss of condition (wasting/cachexia), and chronic inflammatory response are characteristic of FIV infection (Ackley et al, 1990;Barlough et al, 1991;Brown et al, 1991;Diehl et al, 1995;Egberink et al, 1992;Hutson et al, 1991;Kohmoto et al, 1998;Matsumura et al, 1993;Novotney et al, 1990;Sundberg et al, 2000;Tompkins et al, 1991;Torten et al, 1991;Willett et al, 1993;Yamamoto et al, 1989). Progressive stages can last months to years after initial infection, during which time the cat may be an asymptomatic carrier or may exhibit persistent generalized lymphadenopathy, AIDS-related complex, or feline AIDS (Bendinelli et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased CD4 T-cell counts in infected cats have been reported in both natural and experimental infections (Ackley et al, 1990;Hoffmann-Fezer et al, 1992). However, select FIV vaccine strains consistently produce clinical illness characterized by recurrent high fever, increased incidence of secondary infection, leukopenia, CD4 loss, and CD4/CD8 inversion (Callanan et al, 1992;Diehl et al, 1995). Even with the loss of CD4 T-cells, cytotoxic T-lymphocyte (CTL) activities develop early in FIV infections and persist during the asymptomatic stage, similar to HIV-1 infections (Song et al, 1992).…”
Section: Pathogenesis and Infectionmentioning
confidence: 99%
“…The duration of the reduced viral load is still unknown (Johnston and Flores, 2001;Mooij and Heeney, 2002). High-dose in vivo inoculum and/or early passages of select FIV strains have consistently caused clinical illness in addition to CD4 loss and CD4/CD8 inversion (Callanan et al, 1992;Diehl et al, 1995). The use of a high-dose challenge or a highly virulent challenge strain may require modi®cations in the standard of judging vaccine ef®cacy, since no vaccine may be able to provide complete protection against such a rigorous challenge.…”
Section: Implication Of Challenge Studiesmentioning
confidence: 99%
“…Natural and experimental infection of cats with biological and molecularly cloned isolates of FIV consistently induce an acute viremia associated with T-cell alterations including depressed CD4 : CD8 T-cell ratios and CD4 T-cell depletion. [4][5][6][7]10,11,21,[190][191][192][193][194] Early studies revealed that targets for FIV in vitro and in vivo included CD4 T-cells, macrophages, dendritic cells, microglia, and astrocytes similar to those for HIV infection in humans, but also included CD8 T-cells, and B-cells (Table II). 4,18,23,186,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] Early reports also demonstrated that continuous passage of particular FIV isolates in cell culture selected for virus variants capable of replication in feline adherent cell lines, including Crandell feline kidney cells (CrFK) and G355-5 cells, as well as established feline interleukin (IL)-2-independent T-cell lines.…”
Section: Fiv Receptor Usagementioning
confidence: 99%